Analisis Pengaruh Curve Number terhadap Debit BanjirMenggunakan Metode Pemodelan Hidrologi di DAS Juana: Analysis Curve Number Influence on Flood Discharge using Hydrological Modeling in Juana Watershed - Komara, Kresna Dwiki; Kurniyaningrum, Endah; Rinanti, Astri; Yuwono, Bambang Endro; Pontan, Darmawan (Technomedia Journal, 2025)
This research aims to investigate the effect of Curve Number (CN) on flood discharge in the Juana watershed. Using a case study approach, analysis was carried out to understand the relationship between CN values and hydrological characteristics and flood risk in the region. The research method involves hydrological modeling which takes into account the CN value as a key parameter. Spatial and temporal data on land cover, soil type and vegetation are used to determine CN values in various land change scenarios. The study results indicate a trend of increasing Curve Number (CN) values in 5 Subwatersheds, a decrease in 2 Subwatersheds, and no change in 1 Subwatershed. The highest increase in CN value was observed in the Juana 2 Subwatershed, with an increase of (+) 0.935, while the largest decrease was found in the Gembong Subwatershed, with a decrease of (-) 0.349. Both the increase and decrease in CN values are directly proportional to the resulting flood discharge. These findings have important implications for disaster risk management, regional planning, and sustainable policy development in the Juana River Basin and similar regions worldwide. By understanding more deeply the influence of CN on flood discharge, more effective mitigation measures can be designed to protect communities and ecosystems that are vulnerable to flood threats.